Consumption Behaviour of Fuelwood in Gujarat - Khanna, Pradeep; Mahendra, A. K. (Indian Forester, 1995)
Several studies have been conducted to study the consumption behaviour of fuelwood in different- areas. Present study has been conducted for Gujarat to corroborate or contradict their findings. Trend of demand and supply have been studied. Factors responsible for quantity of firewood consumption viz. population, forest area and number of cattle in rural areas of have been studied with the help of regression analysis. Distance from forests i.e. easy availability of firewood have significant effect on per capita consumption of fuelwood. Cattle number in the areas having forests have much effect on per capita fuel consumption. Percent contribution of fuel wood is less in urban areas in comparison to rural areas due to use of alternative sources of energy. Development and publicity of alternative sources of energy is essential for the rural areas.